2013
DOI: 10.1177/1938640012473150
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate and Long-Term Outcomes of the Suture Bridge Technique for the Management of Insertional Achilles Tendinopathy

Abstract: The central incision with complete detachment of the Achilles tendon and reattachment with the suture bridge technique for the treatment of insertional Achilles tendinopathy provides an effective treatment with good to excellent clinical outcomes in 97% of patients, with a mean follow-up of 29 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…5 Complete avulsion of the tendon occurs in other situations such as avulsion fracture of the calcaneal tuberosity 11 and surgery for insertional Achilles tendinopathy that necessitates complete detachment of the tendon to excise the degenerated portion. 9,15,17 Double-row suture bridge fixation is a technique for repairing tendon-bone junctions and is widely used for rotator cuff repair. 16,18 This technique also has been introduced for the reattachment of the Achilles tendon insertion.…”
Section: Technique Tipmentioning
confidence: 99%
“…5 Complete avulsion of the tendon occurs in other situations such as avulsion fracture of the calcaneal tuberosity 11 and surgery for insertional Achilles tendinopathy that necessitates complete detachment of the tendon to excise the degenerated portion. 9,15,17 Double-row suture bridge fixation is a technique for repairing tendon-bone junctions and is widely used for rotator cuff repair. 16,18 This technique also has been introduced for the reattachment of the Achilles tendon insertion.…”
Section: Technique Tipmentioning
confidence: 99%
“…50 Complications resulting from this procedure have ranged from 6 to over 30 percent in the literature and are most commonly due to wound healing issues, painful scar, or sural nerve injury. 32,42,43,49,67,68 …”
Section: Operative Treatmentmentioning
confidence: 99%
“…Despite only having short-term follow-up data at 6 or 12 weeks, the 70% rate of patient satisfaction with percutaneous ultrasonic tenotomy for IAT in this series was similar to the rates in other studies of tendinopathy at the elbow, which reported ranges from 75% to 100%. 2,4,7 In comparison, the satisfaction rate for surgical debridement of IAT is generally greater than 87%, [10][11][12][13][14][15][16][17][18] yet this high patient satisfaction rate also had complication rates ranging from 6% to greater than 30%, which included wound-healing issues (superficial would infection, skin necrosis, hematoma, and delayed wound healing), scar abnormalities (hypersensitivity, hypertrophy, and numbness), sural nerve injury, tendon avulsion, deep venous thrombosis, and recurrence of pain. 10,11,[13][14][15][16] There are several advantages of percutaneous ultrasonic tenotomy relative to an open or endoscopic surgical procedure.…”
Section: Discussionmentioning
confidence: 99%